Prevalence of GBV-C RNA in HIV infected individuals in Tehran, Iran - H Keyvani; A Mohammadi; M Haji-abdolbaghi (Tehran University of Medical Sciences, 2010)
"nBackground: GB virus C (GBV-C) is a flavivirus that was characterized in 1995. The prevalence of GBV-C RNA in HIV-infected subjects has not been previously studied in Iran and was therefore determined."nMethods: We have investigated serum samples of 80 patients from Imam Khomeini Hospital, Tehran, Iran, whose HIV infection was confirmed in our laboratory by Western-blotting. We used nested-PCR to detect GBV-C/HGV RNA in their sera."nResults: GBV-C/HGV RNA was detected in 15 (18.8%) of 80 patients. There was no significant difference in GBV-C/HGV RNA prevalence between males and females, in different age groups and HIV viral loads groups."nConclusion: The prevalence of GBV-C RNA was high in HIV-infected patients. There was no association between GBV-C RNA prevalence and specific gender, age, and HIV viral loads groups.